Cryorolling and warm forming of AA6061 aluminum alloy sheets. Issue 12 (10th September 2017) - Satish, D. Raja; Feyissa, Fitsum; Kumar, D. Ravi
ABSTRACT: Cryorolling is a severe plastic deformation (SPD) process used to obtain ultrafine-grained aluminum alloy sheets along with higher strength and hardness than in conventional cold rolling, but it results in poor formability. An alternative method to improve both strength and formability of cryorolled sheets by warm forming after cryorolling without any post-heat treatment is proposed in this work. The formability of cryorolled AA6061 Al alloy sheets in the warm working temperature range is characterized in terms of forming limit diagrams (FLDs) and limiting dome height (LDH). Strain distributions and thinning in biaxially stretched samples are studied. Hardness of the formed samples is correlated with ultimate tensile strength to estimate post-forming mechanical properties. The limit strains and LDH have been found to be higher than in the case of the conventional processing route (cold rolled, annealed and formed at room temperature), making this hybrid route capable of producing sheet metal parts of aluminum alloys with high strength and formability. In order to combine the advantages of enhanced formability and better post-forming strength than the conventional cold rolled and annealed sheets, warm forming at 250°C has been found to be suitable for this alloy in the temperature range that has been studied.